2023
DOI: 10.1172/jci.insight.160578
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline-induced disruption of the intestinal FXR/FGF15 axis impairs osteogenesis in mice

Abstract: Antibiotic-induced shifts in the indigenous gut microbiota influence normal skeletal maturation. Current theory implies that gut microbiota actions on bone occur through a direct gut-bone signaling axis. However, our prior work supports that a gut-liver signaling axis contributes to gut microbiota effects on bone. Purpose was to investigate the effects of minocycline, a systemic antibiotic treatment for adolescent acne, on pubertal/postpubertal skeletal maturation. Sex-matched specific-pathogen-free(SPF) and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 103 publications
(338 reference statements)
0
4
0
Order By: Relevance
“…Here we found that both the adolescent group-housed and socially isolated males exposed to adolescent minocycline treatment displayed a decrease in social preference compared to their baseline controls. While this result may seem to conflict with previous findings demonstrating minocycline's protective effects following behavior impairments, administration of the drug has shown to lead to adverse reactions in some cases, potentially attributed to antibiotic induced shifts in the microbiota [42,54,55]. In addition to the potential aversive effects, minocycline treatment has also shown to lead to reductions in locomotor behavior in rodents [56][57][58].…”
Section: Adolescent Minocycline Treatment Diminishes Social Preferenc...mentioning
confidence: 64%
“…Here we found that both the adolescent group-housed and socially isolated males exposed to adolescent minocycline treatment displayed a decrease in social preference compared to their baseline controls. While this result may seem to conflict with previous findings demonstrating minocycline's protective effects following behavior impairments, administration of the drug has shown to lead to adverse reactions in some cases, potentially attributed to antibiotic induced shifts in the microbiota [42,54,55]. In addition to the potential aversive effects, minocycline treatment has also shown to lead to reductions in locomotor behavior in rodents [56][57][58].…”
Section: Adolescent Minocycline Treatment Diminishes Social Preferenc...mentioning
confidence: 64%
“…Media was changed to stimulate cells with 50 ng/mL phorbol 12‐myristate 13‐acetate (Stemcell Technologies, Vancouver, Canada), 1 μg/mL ionomycin (Stemcell Technologies) and 2 μM monensin (Thermo Fisher Scientific) for 4 h. Cells were harvested, washed, counted and re‐suspended in flow cytometry buffer. Cells were treated with FcR‐block (Miltenyi Biotec, Bergisch Gladbach, Germany) and labelled for surface antibodies, per manufacturer's instructions as previously reported (Carson et al, 2023; Swanson et al, 2021). Dead cells were excluded via labelling with LIVE/DEAD 405‐nm Fixable Yellow Stain (Thermo Fisher Scientific), per manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…cytometry buffer. Cells were treated with FcR-block (Miltenyi Biotec, Bergisch Gladbach, Germany) and labelled for surface antibodies, per manufacturer's instructions as previously reported (Carson et al, 2023;Swanson et al, 2021). Dead cells were excluded via labelling with LIVE/ DEAD 405-nm Fixable Yellow Stain (Thermo Fisher Scientific), per manufacturer's instructions.…”
Section: S Gingival Bacteriome Analysismentioning
confidence: 99%
“…3389/fmicb.2023.1124945 Frontiers in Microbiology 07 frontiersin.org knockout mice exhibits osteopenia phenotype, suggesting its positive effect in bone remodeling (Bozadjieva-Kramer et al, 2021). Application of antibiotics minocycline can lead to impaired skeletal maturation in young mice, likely due to excessive serum conjugated BAs resulted from gut microbiota dysbiosis and disrupted FXR-FGF15 axis (Carson et al, 2022).…”
Section: Bile Acidsmentioning
confidence: 99%